DEPRESSION STATUS AMONG 14-15 YEAR OLD STUDENTS AT PHUNG CHI KIEN SECONDARY SCHOOL, HUNG CHAU COMMUNE, NGHE AN PROVINCE AND SOME RELATED FACTORS (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current status of depression among 14-15-year-old students at Phung Chi Kien Secondary School and identify some related factors in 2025Methods: A cross-sectional descriptive study was conducted using the depression, anxiety, and stress screening tool (DASS - 21) on 400 8th and 9th-grade students (aged 14-15) at Phung Chi Kien Secondary School, Nghe An province.Results: The prevalence of depression among 14 to 15-year-old students at Phung Chi Kien Secondary School was 38.8%. Among students experiencing depression, mild depression accounted for the highest proportion at 44.5%, followed by moderate (30.3%), severe (13.6%), and extremely severe (11.6%). Factors associated with depressive symptoms in students included conflicts with parents (OR = 2.776), feeling pressured by parental expectations (OR = 2.130), perceiving a lack of care from teachers (OR = 2.810), and feeling disappointed with academic performance (OR = 1.933).Conclusion: Depression is a common mental health issue among secondary school students, strongly impacted by pressures from family and the school environment. Therefore, it is necessary to have appropriate support measures from both the school and the family, especially for children in high risk groups.
Keywords: Depression, secondary school students, DASS-21.